PENGOLAHAN ARSIP KASET DI KANTOR ARSIP DAN PERPUSTAKAAN DAERAH KOTA YOGYAKARTA - , DANU PUNKY WICAKSONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Writing of this report entitled \"The Arrangement of Archive Cassete in Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta\" is the result of data collection Field Work Practices are held at Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta. Field Work Practice has the goal to find a picture on archive cassete and to specifically examine the archive cassete processing procedures. The scope of the problem, among others, how the arrangement of archive cassete, the means used, and what are the obstacles encountered when processing the archive cassete. The method used in the study or practice of fieldwork was partly through Library Studies, Participation observation and interviews. Interview method aims to obtain more detailed information from speakers who are experts in the field of archives. In practice the implementation of the Job writer can directly observe and participate in the processing of archive cassete available in Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta. With these methods will obtain complete data. It is to know the extent of the application of archival science with the reality on the ground. The conclutions of the arrangement of archive cassete in Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta, among others, has been un complete, because there was no the regulations of the processing archive cassete, the descriptions form of archive cassete and the arrengement of archive cassete facilities were limited.